Union commitment as a predictor of member participation in union activities - Md Ismail, Md Fauzi; Yahya, Khulida Kirana; Daud, Zulkiflee (Penerbit Universiti Utara Malaysia, 2008)
This study examined the relationship between union commitment and union participation. It also attempted to determine the most important dimension of union commitment in explaining union participation. Data were gathered through a survey of transportation union members in Malaysia. Correlation and regression analyses were used to examine the relationship. Findings showed that dimensions of union commitment, namely membership and efforts towards union, union loyalty, responsibility to the union, belief in unionism, and pride and confidence to union, were correlated with union participation. However, the regression result indicated that only union loyalty was found to be the most significant factor that explained union participation. Implications of the findings are also discussed.